MODELS OF THE SEMANTIC INTERPRETATION OF TEXTS - Литвиненко, О. Є.; Бурко, Д. А. (Science-based technologies, 2010)
The paper deals with considering of the main technologies of text analysis in computer systems. The efficient methods of the semantic analysis and semantic processing of texts was distinguished. The approach is based on the defining of semantic levels.